First camera survey in Burkina Faso and Niger reveals human pressures on mammal communities within the largest protected area complex in West Africa. Issue 5 (29th July 2019) - Harris, Nyeema C.; Mills, Kirby L.; Harissou, Yahou; Hema, Emmanuel M.; Gnoumou, Isaac T.; VanZoeren, Jenna; Abdel‐Nasser, Yayé I.; Doamba, Benoit
Abstract: The dearth of ecological data from protected areas at relevant scales challenges conservation practice in West Africa. We conducted the first camera survey for Burkina Faso and Niger to elucidate interactions between resource users and mammals in the largest protected area complex in West Africa (W‐Arly‐Pendjari, WAP). We differentiated direct (e.g., poaching) and indirect (e.g., domestic animals) human activities to determine their effects on species richness, composition, and behavior. Livestock was the dominant human pressure while gathering was the most prevalent direct human activity. Human pressure did not influence species richness or composition, but reduced mammal activity with greater consequences from indirect activities. We also found distinct differences among guilds in their behavioral responses to human pressures as wild ungulates exhibited the greatest sensitivities to livestock presence. Our findings, that aggregated socioecological data, transition the WAP complex from the singular mandate of nature conservation to a dynamic coupled human‐natural ecosystem.